Álgebras com identidades polinomiais - Massano, Isabela Monteiro (Universidade Federal de São Carlos, 2023)
In this work, basic definitions and results on Algebras with Polynomial Identities are introduced, some classic results of the theory that involve them are stated and demonstrated, such as the Amitsur-Levitzki Theorem, according to Rosset [4]. Furthermore, we describe a basis for the ideal of the Zn-graded identities of the matrix algebra n × n over a field of characteristic zero.
Algebras with polynomial identities
Keywords: Álgebras; Identidades polinomiais; Álgebras graduadas; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA::GRUPOS DE ALGEBRA NAO-COMUTAVIVA